2006
DOI: 10.1002/j.2168-9830.2006.tb00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Problem Solving in Engineering: Lessons for Engineering Educators

Abstract: Practicing engineers are hired, retained, and rewarded for solving problems, so engineering students should learn how to solve workplace problems. Workplace engineering problems are substantively different from the kinds of problems that engineering students most often solve in the classroom; therefore, learning to solve classroom problems does not necessarily prepare engineering students to solve workplace problems. These qualitative studies of workplace engineering problems identify the attributes of workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
606
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(621 citation statements)
references
References 27 publications
11
606
0
4
Order By: Relevance
“…Studies of practicing engineers show a shift from a purely technical focus towards an increasing appreciation of social and environmental factors. See also Jonassen et al [11] and Lethbridge [12] for discussions of the current dielectic between education and practice in engineering. Issues related to ancillary skills which might be acquired "accidentally" are discussed by Walther and Radcliffe and Berggren et al [1,15] There is a small but growing body of literature on college students' understanding of engineering and engineering practice.…”
Section: Related Workmentioning
confidence: 99%
“…Studies of practicing engineers show a shift from a purely technical focus towards an increasing appreciation of social and environmental factors. See also Jonassen et al [11] and Lethbridge [12] for discussions of the current dielectic between education and practice in engineering. Issues related to ancillary skills which might be acquired "accidentally" are discussed by Walther and Radcliffe and Berggren et al [1,15] There is a small but growing body of literature on college students' understanding of engineering and engineering practice.…”
Section: Related Workmentioning
confidence: 99%
“…Engineers, in practice, are paid to solve problems (Jonassen, Strobel, & Lee, 2006). However, the well-structured, constrained problems that engineering students solve in the classroom fail to prepare them for the complexity of ill-structured workplace problems (Henry, Jonassen, Winholtz, & Khanna, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative study by Jonassen et al (2006), which examined real engineering problems in the context of engineering education, concluded that "because solving well-structured problems in science and engineering classrooms does not readily lead to solving complex, ill-structured workplace problems, engineering programs must support learning to solve complex, ill-structured workplace problems if they are to prepare their graduates for future learning and work". The action learning environment established for undergraduate mechanical engineering student project work in the present study supported the learning of skills required for more than straightforward right-answer problem-solving, rote learning and simplistic approaches to complex situations.…”
Section: Discussionmentioning
confidence: 99%